Isolated word recognition using neural networks - Filipovič, Mark (Lietuvos matematikos rinkinys, 2003)
This paper presents the speech recognition system, designed for recognition of 50 isolated Lithuanian words. The system is based on feedforward neural networks trained by error backpropagation algorithm. Speaker dependent speech recognition was investigated. The article presents analysis of the developed system parameters influence on the accuracy of word recognition. Experimental results showed that proposed system could be used for isolated word recognition.